2022
DOI: 10.3390/healthcare10030529
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Pneumo-Mediastinum in a Post-COVID-19 Patient with Systemic Sclerosis

Abstract: Pulmonary involvement is the most common cause of death among patients with systemic sclerosis (SSc). The current coronavirus disease 2019 (COVID-19) is particularly problematic to manage in SSc patients since they may experience a more severe evolution of COVID-19 due to the pre-existent interstitial lung disease (ILD) and the administration of immunosuppressive treatments. In addition, the remarkable radiological similarities between SSc-ILD and COVID-19 complicate the differential diagnosis between these tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 39 publications
(76 reference statements)
0
4
0
Order By: Relevance
“…SSc is a complex autoimmune connective tissue disease affecting the skin, gastrointestinal tract, and lungs, which carries potentially life-threatening complications [ 18 , 19 ]. Microvascular changes with endothelial cell dysfunction, followed by their transition into myofibroblasts, are central in the pathogenesis of the disease [ 20 , 21 ].…”
Section: Calcinosis Cutis and Systemic Sclerosismentioning
confidence: 99%
“…SSc is a complex autoimmune connective tissue disease affecting the skin, gastrointestinal tract, and lungs, which carries potentially life-threatening complications [ 18 , 19 ]. Microvascular changes with endothelial cell dysfunction, followed by their transition into myofibroblasts, are central in the pathogenesis of the disease [ 20 , 21 ].…”
Section: Calcinosis Cutis and Systemic Sclerosismentioning
confidence: 99%
“…In addition, the authors described some common features among COPD patients with eosinophil counts persistently ≥2% (i.e., older age, male gender, fewer current smokers, higher FEV 1 % predicted, higher fat-free mass index, fewer symptoms, and lower BODE (body mass index, airflow obstruction, dyspnoea, exercise capacity index) [ 142 ]. Interestingly, in the ECLIPSE study, although the subjects with high blood eosinophil counts had better clinical characteristics at baseline, they also showed increased rate of emphysema progression, further confirming the pathogenetic role of this cell in airway inflammation, tissue damage, and remodeling [ 142 , 143 ]. In addition, exploring the relationship between lung function and sputum eosinophilia, several studies have shown a link between airway obstruction and eosinophilic lung inflammation.…”
Section: Eosinophils and Chronic Obstructive Pulmonary Diseasementioning
confidence: 93%
“…Systemic sclerosis (SSc) and COVID-19 share radiological signs, complicating the differentiation between these two entities [ 59 ]. It is critically important to timely identify pulmonary changes to prevent severe complications.…”
Section: Systemic Sclerosis and Long Covidmentioning
confidence: 99%